Do memories of the Ebola virus disease outbreak influence post-Ebola health seeking behaviour in Guéckédou district (epicentre) in Guinea? A cross-sectional study of children with febrile illness - Camara, Bienvenu Salim (BMC Public Health, 2020)
BACKGROUND: The 2013–2015 Ebola Virus Disease (EVD) outbreak in Guinea resulted in community mistrust that influenced health care service utilization. This study aimed to assess whether EVD-related memories affect post-outbreak health-seeking behaviours for children under 5 years of age with febrile illnesses in Guéckédou district, Guinea. METHODS: This cross-sectional study was conducted by surveying caregivers of children under 5 years of age in the sub-district most affected by the EVD outbreak (Guèndembou) and the least affected sub-district (Bolodou) in Guéckédou district. Memories of the outbreak were referred to as EVD-related fears in the post-EVD period, which was based on a series of questions regarding current feelings. RESULTS: While the majority of caregivers sought care for their children with febrile illness in both districts, a statistically significantly higher proportion of caregivers in Guèndembou sought care, compared to caregivers in Bolodou.. More caregivers in Guèndembou (19.9%; n = 39) reported the death of family members or friends due to EVD compared to Bolodou (6.9%; n = 14; P < 0.001). The mean EVD fear score of caregivers was significantly higher in Guèndembou (3.0; SD: 3.0) than in Bolodou (2.0; SD: 1.1) (p < 0.001). Caregivers with a fear score above the median were 1.68 times more likely to seek care than those whose fear score was equal to or below the median; however, this difference was not statistically significant. Caregivers who reported family members’ or friends’ death due to EVD were also more likely to seek care (AOR = 2.12; 95%CI: 0.91–4.91), however, with no statistical significance. Only residing in the EVD-most affected sub-district of Guèndembou (AOR = 1.74; 95%CI: 1·09–2.79) was positively associated with seeking care. CONCLUSIONS: This study reveals that community members in the rural district of Guéckédou still live with fear related to EVD nearly 2 years after the outbreak. It calls for more efforts in the health domain to preserve communities’ key values and address the psychosocial effect of EVD in rural Guinea.